2005
DOI: 10.1007/s00244-004-0174-1
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Metabolic Enzymes in Australian Bass, Macquaria novemaculeata, After Exposure to Petroleum Hydrocarbons

Abstract: Australian bass Macquaria novemaculeata were exposed to the water-accommodated fraction of Bass Strait crude oil, dispersed crude oil, or burnt crude oil to assess sublethal effects of oil spill remediation techniques on fish. Fish were exposed to these treatments for 16 days either through the water column or by way of a pre-exposed diet of amphipod Allorchestes compressa. Fish gills, liver, and white muscle were sampled and cytochrome C oxidase (CCO) and lactate dehydrogenase (LDH) activities quantified. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Anaerobic capacity was most impacted in the tissues of fish collected from heavily polluted sites with the LDH activity in the tissues of fish from downstream river Nile higher than that of fish sampled from upstream river Nile. Liver and muscles of Nile tilapia seem to be able to react strongly to the presence of higher chemical pollution by increasing anaerobic capacity, possibly facilitating elimination of offending chemicals [44]. LDH activity in muscle was always higher than that in liver.…”
Section: Discussionmentioning
confidence: 91%
“…Anaerobic capacity was most impacted in the tissues of fish collected from heavily polluted sites with the LDH activity in the tissues of fish from downstream river Nile higher than that of fish sampled from upstream river Nile. Liver and muscles of Nile tilapia seem to be able to react strongly to the presence of higher chemical pollution by increasing anaerobic capacity, possibly facilitating elimination of offending chemicals [44]. LDH activity in muscle was always higher than that in liver.…”
Section: Discussionmentioning
confidence: 91%
“…However, in general, a low acute toxicity of burn residue WAFs to marine invertebrate species has been observed (Faksness et al 2012). Besides invertebrate species, also different fish species have been exposed to WAFs from ISB experiments (Bender et al 2018;Cohen 2001;Cohen et al 2005). The studies mainly have found a low toxic potential (Cohen et al 2005).…”
Section: Cewaf Ifo180mentioning
confidence: 99%
“…Besides invertebrate species, also different fish species have been exposed to WAFs from ISB experiments (Bender et al 2018;Cohen 2001;Cohen et al 2005). The studies mainly have found a low toxic potential (Cohen et al 2005). However, also delayed effects after a recovery phase such as reproductive impact have been observed in fish that have been exposed to burn residues for a short period (Bender et al 2018).…”
Section: Cewaf Ifo180mentioning
confidence: 99%
See 1 more Smart Citation
“…Feed sources provided during this study varied: nauplii and zoea were provided with algae, mysis with rotifers, and postlarvae with commercial pellets. Exposure of WAFs or CEWAFs through either the water column or exposed feed resulted in similar alterations of metabolic enzymes in fish [38]. The addition of small quantities of feed may have resulted in larvae being exposed to oil contaminants through both the water column via the gills and the digestive tract via ingestion.…”
Section: Survivalmentioning
confidence: 99%